Domestic Facemask Waste Policy Based on Environmental Ethics in the Covid-19 Pandemic: Urgency and Challenges - Absori; Quinncilla KH; Nugroho HSW; Budiono A (Dove Medical Press, 2024)
Absori,1 Kiara Hanna Quinncilla,1 Heru Santoso Wahito Nugroho,2 Arief Budiono1 1Department of Law, Universitas Muhammadiyah Surakarta, Surakarta, Indonesia; 2Department of Midwifery, Poltekkes Kemenkes Surabaya, Surabaya, IndonesiaCorrespondence: Arief Budiono, Universitas Muhammadiyah Surakarta, Surakarta, A Yani Street, Pabelan, Surakarta, 57102, Indonesia, Email ab368@ums.ac.idIntroduction: The Covid-19 pandemic greatly affected various aspects of life. To prevent and control its spread, people are morally and legally obliged to wear face facemasks. The use of facemasks brings many waste problems. However, the Indonesian policy on facemask waste management does not regard the massive environmental consequences, as the amount of domestic facemask waste reaches hundreds of tons daily with limited management capacity application. Hence, this study aims to assess current issues and policies on facemask waste from the perspective of environmental ethics.Methods: This research used the juridical-normative method, where legal rules and principles were processed to address current issues, supported by literature sources. This research employed qualitative approach to collect and analyze data.Results: Results showed that there was a legal void which caused terrible facemask waste management in Indonesia. There was confusion in categorizing facemask waste, whether it is domestic or infectious waste, causing hazards in its management. From a deep ecology perspective, the applied facemask waste management was only beneficial for humans while completely neglecting biotic and abiotic components. To overcome this, several suggestions were: 1) categorizing domestic disposable facemask waste as hazardous waste, 2) applying sanctions for the violation of norms and tight social control on first-level management of facemask waste, and 3) using reusable facemask.Conclusion: The obligation of wearing facemasks that were protective for humans during the Covid-19 pandemic must be followed with policies regulating facemask waste management that consider the environment and its biotic and abiotic components.Keywords: policy, facemask, waste, covid 19, environment, health